Critical Study on Significance of Yoga and Asanas: Exploring the Role of Yoga and Asanas in Education (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Education is culture transmission. Educationalists across the globe have, at various periods in human history, described education in different ways. Aristotle described education in a sound body as the development of a sound mind. Nothing can be as critical as the kids, because they are the world's future. Whether they grow up depends on what basic education they get from the elementary school. The cycle of teaching and learning is no longer limited to the four walls of a classroom.